2023
DOI: 10.1111/cgf.14770
|View full text |Cite
|
Sign up to set email alerts
|

Directionality‐Aware Design of Embroidery Patterns

Abstract: Embroidery is a long‐standing and high‐quality approach to making logos and images on textiles. Nowadays, it can also be performed via automated machines that weave threads with high spatial accuracy. A characteristic feature of the appearance of the threads is a high degree of anisotropy. The anisotropic behavior is caused by depositing thin but long strings of thread. As a result, the stitched patterns convey both color and direction. Artists leverage this anisotropic behavior to enhance pure color images wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Recently, Bitton et al (2023) propose a visual analogies dataset, VASR, where they found that models struggle to find out analogies when given carefully chosen distractors. In computer graphics, some graphics design algorithms take as input an image from the user, and transform it to some other types of visual designs that are similar to the given image, such as embroidery patterns (Zhenyuan et al, 2023) and vector line arts (Mo et al, 2021). This category of work establishes connections between images and application-specific graphics patterns.…”
Section: A5 Miscellaneousmentioning
confidence: 99%
“…Recently, Bitton et al (2023) propose a visual analogies dataset, VASR, where they found that models struggle to find out analogies when given carefully chosen distractors. In computer graphics, some graphics design algorithms take as input an image from the user, and transform it to some other types of visual designs that are similar to the given image, such as embroidery patterns (Zhenyuan et al, 2023) and vector line arts (Mo et al, 2021). This category of work establishes connections between images and application-specific graphics patterns.…”
Section: A5 Miscellaneousmentioning
confidence: 99%